112k views
2 votes
Solve using the substitution method.​

Solve using the substitution method.​-example-1
User Sayonti
by
4.4k points

2 Answers

4 votes

Answer:

d=3, e=-1

Explanation:

Solve using the substitution method.​-example-1
User Greg Bulmash
by
4.9k points
1 vote

Answer:

The solution is d = 3 and e = -1

Explanation:

To solve using the substitution method, we need to first solve the second equation for d.

d - e = 4

d = e + 4

Now that we have the value of d, we can put it in for d in the first equation and solve for e.

d + e = 2

(e + 4) + e = 2

2e + 4 = 2

2e = -2

e = -1

Now that we have this value, we can plug it into the original equation and find d.

d + e = 2

d + -1 = 2

d = 3

User Vahid Al
by
4.7k points